2018
DOI: 10.1096/fj.201801401r
|View full text |Cite
|
Sign up to set email alerts
|

Mdm2‐p53‐SF1 pathway in ovarian granulosa cells directs ovulation and fertilization by conditioning oocyte quality

Abstract: Functions of tumor suppressor p53 and its negative regulator mouse double minute 2 homolog (Mdm2) in ovarian granulosa cells remain to be elucidated, and the current study aims at clarifying this issue. Mice with Mdm2 deficiency in ovarian granulosa cells [Mdm2‐loxP/progesterone receptor (Pgr)‐Cre mice] were infertile as a result of impairment of oocyte maturation, ovulation, and fertilization, and those with Mdm2/p53 double deletion in granulosa cells (Mdm2‐loxP/p53‐loxP/Pgr‐Cre mice) showed normal fertility,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…Recently, Haraguchi et al (2019) found that in murine ovarian cumulus granulosa cells, the mouse double minute 2 homolog (Mdm2) - steroidogenic factor 1 (SF1) pathway played an important role in oocyte maturation by suppressing p53 activation; deletion of Mdm2 gene expression led to the activation of p53 [ 33 ]. We, however, did not observe differences in the expression of Mdm2 and SF1 in mural granulosa cells of healthy and atretic antral follicles (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Haraguchi et al (2019) found that in murine ovarian cumulus granulosa cells, the mouse double minute 2 homolog (Mdm2) - steroidogenic factor 1 (SF1) pathway played an important role in oocyte maturation by suppressing p53 activation; deletion of Mdm2 gene expression led to the activation of p53 [ 33 ]. We, however, did not observe differences in the expression of Mdm2 and SF1 in mural granulosa cells of healthy and atretic antral follicles (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In Pgr ‐Cre female mice, Cre recombinase is expressed not only in the uterus but in the ovary (Soyal et al , 2005). Although Pgr ‐Cre mouse line can be used for deletion of the floxed gene in the entire uterus (Matsumoto et al , 2018), the events regulated by ovarian functions such as ovulation and fertilization need to be evaluated in the pregnant mouse models using Pgr ‐Cre females (Haraguchi et al , 2019). Mice with deletion of Rb1 in the whole uterus ( Rb1 d/d mice) were generated by crossing Pgr ‐Cre with Rb1 ‐floxed mice.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA extraction was performed as described previously 4,6,38,42,43 . The complementary DNA were synthesized from the extracted RNA using ReverTra Ace qPCR RT Master Mix (TOYOBO), and, and qPCR was performed using SYBR Green PCR Master Mix (Thermo Fisher Scientific).…”
Section: Evaluation Of Pdsmentioning
confidence: 99%